Thermal affinity as the dominant factor changing Mediterranean fish abundances. (1st September 2017) - Givan, Or; Edelist, Dor; Sonin, Oren; Belmaker, Jonathan
Abstract: Recent decades have seen profound changes in species abundance and community composition. In the marine environment, the major anthropogenic drivers of change comprise exploitation, invasion by nonindigenous species, and climate change. However, the magnitude of these stressors has been widely debated and we lack empirical estimates of their relative importance. In this study, we focused on Eastern Mediterranean, a region exposed to an invasion of species of Red Sea origin, extreme climate change, and high fishing pressure. We estimated changes in fish abundance using two fish trawl surveys spanning a 20‐year period, and correlated these changes with estimated sensitivity of species to the different stressors. We estimated sensitivity to invasion using the trait similarity between indigenous and nonindigenous species; sensitivity to fishing using a published composite index based on the species' life‐history; and sensitivity to climate change using species climatic affinity based on occurrence data. Using both a meta‐analytical method and random forest analysis, we found that for shallow‐water species the most important driver of population size changes is sensitivity to climate change. Species with an affinity to warm climates increased in relative abundance and species with an affinity to cold climates decreased suggesting a strong response to warming local sea temperatures over recent decades. This decrease in the abundance of cold‐water‐associated species at the trailing "warm" end of their distribution has been rarely documented. Despite the immense biomass of nonindigenous species and the presumed high fishing pressure, these two latter factors seem to have only a minor role in explaining abundance changes. The decline in abundance of indigenous species of cold‐water origin indicates a future major restructuring of fish communities in the Mediterranean in response to the ongoing warming, with unknown impacts on ecosystem function. Abstract : We estimated changes in Mediterranean fish abundance using trawl surveys spanning a 20‐year period, and correlated these changes with estimated sensitivity of species to different stressors. We found that, for shallow‐water species, the most important driver of population size changes is thermal affinity which is used here as a proxy for sensitivity to climate change. Despite the immense biomass of nonindigenous species and the presumed high fishing pressure, these only have a minor role in explaining abundance changes.